Social, Cultural and Economic determinants of HIV/AIDS: A community case report of Bhutan - Lekey Khandu; Tashi Tobgay; Willi McFarland (Shahid Beheshti University of Medical Sciences, 2021)
Background: Bhutan has a low-level HIV epidemic, with sporadic cases across the whole population. Our society is witnessing momentous social and cultural changes coinciding with the arc of the HIV pandemic. Therefore, this paper systematically assesses socio cultural determinants of HIV in Bhutan for appropriate responses to end the AIDS epidemic by 2030. Methods: We reviewed the literature relevant to HIV in Bhutan using appropriate search engines. We adapted Dahlgren and Whitehead's model of social health determinants in the population as a conceptual framework. Results: Young age played the salient role between rapid sociocultural changes and HIV in Bhutan. Most teens are sexually active, has relaxed sexual norms, low condom use, and has multiple sexual partners. Gender identity and sexual orientation are increasingly fluid among transgender and gay/bisexual men. Worksites with migrants and entertainment venues are nexuses for sexual networking resulting in transactional/sex work. Conclusion: Our findings suggest a high potential for a shift from diffuse cases of HIV to more concentrated HIV epidemic. HIV responses need to be tailored specifically for key populations instead of the current generalized approach. We recommend community-based HIV Self Testing and social support to overcome the structural barriers to enhance case diagnosis.